The Changing Nature of Telehealth Use by Primary Care Physicians in the United States. (July 2022) - Callaghan, Timothy; McCord, Carly; Washburn, David; Goidel, Kirby; Schmit, Cason; Nuzhath, Tasmiah; Spiegelman, Abigail; Scobee, Julia
Introduction: Prior to the COVID-19 pandemic, telehealth utilization was growing slowly and steadily, although differentially across medical specialties in the United States. The pandemic dramatically expanded physician use of telehealth, but our understanding of how much telehealth use has changed in primary care in the United States, the correlates of physician telehealth uptake, and the frequency with which primary care physicians intend to use telehealth after the pandemic are unknown. This paper is designed to assess these important questions. Methods: Using data from an original national survey of 625 primary care physicians conducted from May 14 to May 25, 2021, we investigate the frequency of physician telehealth use before and during the pandemic and intended use after the pandemic. We also assess the correlates of changes in telehealth use by physicians, comparing telehealth use before the pandemic to use during and after the pandemic. Results: The proportion of primary care physicians using telehealth often, jumped from 5.3% (95% CI 3.5, 7.0) before the pandemic to 46.2% (95% CI 42.3, 50.2) during the pandemic. More importantly, over 70% of physicians intended to use telehealth at least occasionally after the pandemic compared to just 18.7% before, with younger physicians, physicians without telehealth training in medical school, and Asian physicians most likely to increase their telehealth use long-term. Discussion: The COVID-19 pandemic has spurred expansion in telehealth use by primary care physicians that will continue to shape care delivery well beyond the pandemic. Policy change could be needed to facilitate this growth of telehealth long-term.